Learning in Good Relations: Navigating Indigenous Art Education with Care and Accountability - Townrow, Brittney (The Canadian Art Teacher / Enseigner les arts au Canada, 2025)
This manuscript shares my experiences as an Indigenous educator walking the path of bringing Indigenous art practices into school settings, sometimes from my own Heiltsuk community and sometimes in collaboration with others. Living and working on Coast Salish territory, I reflect on what it means to share stories, artistic practices, and land-based teachings that are not always my own. Through projects such as spindle whorl design, Métis finger weaving, and natural yarn dyeing, I explore how these experiences have become invitations to learn alongside Knowledge Holders and community members rather than teaching in isolation.This work is not about becoming an expert. It is about holding responsibility for creating space, crediting sources, and fostering conditions where students and educators can enter the work in a good way. I offer this manuscript as a reflection for others, especially those who are unsure of where to begin, to show how art can serve as a site of relationship, respect, and resurgence.